Analisis Beban Kerja Fore-Log Plant B PT XYZ Menggunakan Metode Workload Indicator Of Staffing Needs - Istifadatul Yunaidah; Nur Cahyadi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
PT XYZ is a specialty chemical manufacturing company with various products for Paper, Water Treatment, Oil Mining, Mining, Plastic, Masterbatch, Agriculture, Home Care, and other industries. PT XYZ in planning its Human Resources must be careful to get optimal workers and high work productivity, so a Workload Analysis is needed to optimize the existing workforce at PT XYZ. In the research process, researchers found the phenomenon of multiple positions in the organizational structure of the Logistics Department of PT XYZ, namely by fore log plant B. This research was conducted with a qualitative method with interviews, observations, and data processing of the daily report of the Foreman Logistic Plant B of PT XYZ. The workload analysis method used in this research is the Workload Indicator of Staffing Needs (WISN) method. With the WISN method, the standard workload can be determined to determine the appropriate number of workers. From the results of research conducted in August 2023, it shows that the standard workload fore log plant B is included in the fit or in accordance with the workload standards set by the company, namely 1.3 so that duplicate positions are allowed.